Fécamp et l’architecture en Normandie - Lindy Grant (Tabularia)
In this paper I have tried to place the abbey church of Fecamp in the broad context of romanesque and gothic architecture in Normandy and, where relevant, England. As a necessary prelude to doing so, I briefly survey the complex sequence of building campaigns, and the evidence for their dating, most of which is already well-established. At all stages, the architecture has a distinctly conservative, even deliberately archaic quality, as if there is always a strong awareness of the past, the past of the Norman dukes, the past of the abbey, and the past of the abbey church itself. Nevertheless, the architects and masons were often very eclectic, so that the building plays a very important role in the introduction of new French gothic ideas and forms into the Norman repertoire. The abbey church, especially the fabric built between 1168 and 1219, proved very influential within the duchy, not only within the immediate area, but also, perhaps more surprisingly, in Lower Normandy. It is interesting to note that, while in Capetian France, after 1160, the direction of gothic architecture was set by the great cathedrals, in Normandy that role was taken by Fecamp and St Étienne at Caen, both venerable Benedictine abbeys with close links with the ducal house.